2013
DOI: 10.1590/s1415-43662013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Características morfológicas e produtivas de feijão guandu anão cultivado em solo compactado

Abstract: 1 RESUMOAliado ao uso indiscriminado de maquinários agrícolas, o manejo inadequado altera a densidade natural do solo causando redução em sua qualidade física e, por conseguinte, implicando em efeitos negativos no desenvolvimento de culturas. Assim, objetivou-se avaliar a influência de compactação do solo nas características morfológicas e produtivas de feijão guandu anão (Cajanus cajan L. Mill sp.) cv. IAPAR 43 Aratã. O experimento foi realizado em casa de vegetação na Universidade Federal de Mato GrossoCampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 19 publications
4
16
0
13
Order By: Relevance
“…Studying bean plants (Phaseolus vulgaris L.) in Ultisol Oxisol, [19] stated that plant height is an important indicator to assess the effects of soil compaction in physiological processes of plants. The results observed in this study for the variable plant height of jack beans are in agreement with those found by reference [20], in which there was a significant decrease in plant height of pigeon pea beans (Cajamus cajan) with increasing levels of compression, with a reduction between the lowest and the highest level of bulk density of 51.07% at 33 days after emergence.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Studying bean plants (Phaseolus vulgaris L.) in Ultisol Oxisol, [19] stated that plant height is an important indicator to assess the effects of soil compaction in physiological processes of plants. The results observed in this study for the variable plant height of jack beans are in agreement with those found by reference [20], in which there was a significant decrease in plant height of pigeon pea beans (Cajamus cajan) with increasing levels of compression, with a reduction between the lowest and the highest level of bulk density of 51.07% at 33 days after emergence.…”
Section: Resultssupporting
confidence: 92%
“…Similar results were obtained by reference [20], who observed a reduction in the number of nodules in pigeonpea with increased bulk density levels.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The inoculation of the BR3267 strain contributed positively to the development and production of cowpea when grown on uncompacted soil, becoming more efficient in a management system that has the concern of da Silva et al 2013 preserving macropores of the soil. Inoculation with the combination of the MT8 + MT15 strains provided satisfactory results in both compacted soil and noncompacted soil favoring the production of cowpea in soil with a higher density.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the physical alterations of the soil, which affect the formation of roots and the grain production, increased density can reduce the activity of microorganisms. In a study by Farias et al (2013) with dwarf pigeonpea grown in compacted soil, the formation of nodules showed a reduction of up to 76.82%, and this effect is explained by the change in root mass due to the reduction of the pore spaces, which increases the resistance to the penetration of roots in the soil profile (Hamza and Anderson, 2005).…”
Section: Introductionmentioning
confidence: 99%